Optical Power Monitoring with Ultrahigh Sensitivity in Silicon Waveguides and Ring Resonators - Dong Li; Linjie Zhou; Liangjun Lu; Jianping Chen (IEEE Photonics Journal)
We demonstrate optical power monitoring using a silicon resistor enabled by the surface and defect states-induced photoconductance effect. Ultrahigh optical power detection sensitivity of −40 dBm under a low AC drive voltage of 5 mV is obtained with the facilitation of a lock-in amplifier circuitry. The detection scheme is applied to monitor the resonances in single and coupled-ring resonators. Intracavity resonance spectrum is successfully measured at both the static and the thermal tuning conditions. The demonstration opens a compelling new way for nonintrusive on-chip optical power detection by exploiting doped silicon resistor-based thermooptic heaters.